EFEKTIVITAS STRATEGI FOEME DALAM PROYEK GOOD WATER NEIGHBORS SEBAGAI UPAYA BINA DAMAI KAWASAN TIMUR TENGAH - MUHAMMAD ANDRE ALFARABBY; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The thesis describes the challenge faced by the FoEME (Friends of the Earth Middle East) on the most complex and enduring conflict in the three Middle East states (Yordania, Palestine, and Israel) through GWN (Good Water Neighbors) project to achieve sustainable peace, by utilizing water problems in the Middle East. This research uses pluralism perspective, with International Organization analysis, and Environmental Peace Building Theory. This research is qualitative research, the used technique is collecting file which is used by library observation. The result of this research prove environmental peace building very efective bringing sustainable peace for conflict with two conditions: 1) long conflict; 2) inter states having resources problems. This thesis show in some part to show the multi effect of the GWN project I – IV in the Middle East states.Keywords: Friends of Middle East, Environmental Peace, Peace Building, Water Crisis